Fetal Anomalies and Long-Term Effects Associated with Substance Abuse in Pregnancy: A Literature Review - Viteri, Oscar A.; Soto, Eleazar E.; Bahado-Singh, Ray O.; Christensen, Carl W.; Chauhan, Suneet P.; Sibai, Baha M. (American Journal of Perinatology, 2015)
Objectives Substance abuse in pregnancy remains a major public health problem. Fetal teratogenicity results from the effect of these substances during fetal development, particularly when used in combination. This review will focus on and attempt to clarify the existing literature regarding the association of substance abuse on the development of congenital anomalies and the long-term implications in exposed offspring.Methods Systematic review of available English literature using the PubMed database of all peer-reviewed articles on the subject.Results A total of 128 articles were included in this review. Alcohol was the most common substance associated with fetal anomalies, particularly facial dysmorphisms and alterations in the central nervous system development. Adverse maternal environments associated with risky behaviors and lack of adequate prenatal care precludes the timely detection of fetal anomalies, confounding most studies linking causality. In addition, although methodological differences and limited availability of well-designed trials exist, substance abuse in pregnancy has been associated with adverse long-term outcomes in infant growth, behavior, cognition, language and achievement.Conclusion The literature summarized in this review suggests that drug exposure during pregnancy may increase the risk of congenital anomalies and long-term adverse effects in exposed children and adolescents. These conclusions must be tempered by the many confounders associated with drug use. A multidisciplinary approach is paramount for appropriate counseling regarding the known immediate and long-term risks of substance abuse in pregnancy.
Keywords: marijuana; cocaine; methadone; opioids; amphetamines; pregnancy